Circulating Levels of Interleukin-1 Family Cytokines in Overweight Adolescents. (9th February 2010) - Jung, Christian; Gerdes, Norbert; Fritzenwanger, Michael; Figulla, Hans Reiner
Abstract : Objectives . Obesity and related diseases are dramatically increasing problems, particularly in children and adolescents. We determined circulating levels of different interleukin (IL)-1 family members in normal weight and overweight adolescents. Methods . Seventy male, Caucasian adolescents (13–17 years) were recruited. Thirty-five had a body-mass index (BMI) above the 90th age-specific percentile. IL-1α, IL-1β, IL-1 receptor antagonist (IL-1ra), and IL-18 were determined using multiplex-technology. Results . IL-18 concentrations were higher in the overweight group compared to normal weight (161.6 ± 40.7 pg/ml versus 134.7 ± 43.4 pg/ml, P = .009 ). Concentrations of circulating IL-1β levels were below the detection threshold. IL-18 (R 2 :0.355, P < .01 ) and IL-1ra (R 2 :0.287, P < .05 ) correlated with BMI, whereas IL-1α did not. Conclusions . Accumulating data indicate the importance of the endocrine function of adipose tissue for the pathophysiological consequences of obesity-related co-morbidities. Since IL-18 is involved in the pathogenesis of different cardiovascular diseases, we conclude that IL-18 may represent a link between obesity and related co-morbidities in children and adolescents.